Peranan Tata Kelola Perusahaan dalam Pencegahan Saji Ulang Laporan Keuangan Perusahaan Manufaktur yang Terdaftar di BEI Periode 2017-2021 - Nunuk Novianti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This study aimed to identify the mechanisms of corporate governance can affect misstatement of financial statements, in particular after the implementation of IFRS in financial accounting standards in Indonesia. Especially in manufacturing companies listed in Indonesia Stock Exchange 2017-2021 period. Sampling technique used in this study aimed is purposive sampling with the number of samples used as many as 70 companies. The variables used in this study is the proportion of the Board of the Independent Commissioner (Commissioner), Ownership Structure Institutional (INTSOWN), structure of ownership (BLOCK), Corporate Audit (AUDIT), Company Size (SIZE) and Leverage (LEV) as independent variables, and restatements (RSTM) as the dependent variable. The analytical method used in this research is the logistic regression models. The results of this study indicate that the independent variable The proportion of Independent Commissioners (KOMISARIS) X1, Company Scale (SIZE) X5 and Leverage (LEV) X6 have a significant effect on the dependent variable Restatement (RSTM). While the independent variables Institutional Ownership Structure (INTSOWN) X2, Share Ownership Structure (BLOCK) X3 and Audit Company (AUDIT) X4 have no significant effect on the dependent variable Restatement (RSTM).